Exchange Rate and Inflation Dynamics in Zambia - Roger, Lionel; Smith, Gregory; Morrissey, Oliver (World Bank, Washington, DC, 2017)
This paper investigates the dynamics between the exchange rate and consumer price inflation in Zambia. The analysis uses a structural vector autoregression, with quarterly data for 1995-2014 and a combination of short-run sign- and zero-restrictions to identify relevant global and domestic shocks. The findings suggest that the pass-through of exchange rates to consumer prices depends greatly on the shock that originally caused the exchange rate to fluctuate. Although the price of copper is the most important driver of the exchange rate, the fluctuations it caused are associated with a low pass-through of only about 7 percent. Exchange rate fluctuations caused by monetary shocks come with a pass-through of up to 25 percent. Food inflation is equally affected by genuine exchange rate shocks, but appears more reactive to changes in copper prices or the money supply. Historical variance decomposition shows that, across periods, the main drivers of exchange rate fluctuations varied substantially.